Cellular origin of platelet-derived microparticles in vivo - Rank, Andreas; Nieuwland, Rienk; Delker, Ruth; Köhler, Anton; Toth, Bettina; Pihusch, Verena; Wilkowski, Ralf; Pihusch, Rudolf (Thrombosis research, 2010)
Introduction - Microparticles (MP), presumably of platelet origin, are the most abundant microparticles in blood. To which extent such MP may also directly originate from megakaryocytes, however, is unknown. During hematopoietic stem cell transplantation, patients undergo total body irradiation which leads to an irreversible destruction of hematopoiesis. - Material and Methods - We studied the levels of “platelet-derived” MP (PMP) in 13 patients before and after total body irradiation with 12Gy (4Gy for 3days, dose rate 4.5cGy/min). PMP were isolated and double-stained with annexin V and anti-CD61. In 6 patients, we additionally analyzed MP exposing P-selectin or CD63. - Results - PMP rapidly declined upon total body irradiation, which was 2.4-fold faster than platelet disappearance. In contrast, the kinetics of MP exposing P-selectin or CD63 was comparable to platelets. - Conclusions - Since CD61-positive MP disappear faster than platelets or MP exposing P-selectin or CD63, our data indicate that MP exposing P-selectin or CD63 are likely to originate from platelets, whereas at least a major fraction of CD61-exposing MP is likely to originate from megakaryocytes in vivo.